Relevance of real-time analyzers to determine mitochondrial quality in endothelial cells and oxidative stress in preeclampsia - Nunes, Priscila R. [UNESP]; Oliveira, Pedro F.; Rebelo, Irene; Sandrim, Valeria C. [UNESP]; Alves, Marco G. (Elsevier, 2024)
Oxidative stress and mitochondrial dysfunction are important elements for the pathophysiology of preeclampsia (PE), a multisystemic hypertensive syndrome of pregnancy, characterized by endothelial dysfunction and responsible for a large part of maternal and fetal morbidity and mortality worldwide. Researchers have dedicated their efforts to unraveling the intricate ways in which certain molecules influence both energy metabolism and oxidative stress. Exploring established methodologies from existing literature, shows that these investigations predominantly focus on the placenta, identified as a pivotal source that drives the changes observed in the disease. In this review, we discuss the role of oxidative stress in pathophysiology of PE, as well as metabolic/endothelial dysfunction. We further discuss the use of seahorse analyzers to study real-time bioenergetics of endothelial cells. Although the benefits are clear, few studies have presented results using this method to assess mitochondrial metabolism in these cells. We performed a search on MEDLINE/PubMed using the terms “Seahorse assay and endothelial dysfunction in HUVEC” as well as “Seahorse assay and preeclampsia”. From our research, we selected 16 original peer-review papers for discussion. Notably, the first search retrieved studies involving Human Umbilical Vein Endothelial Cells (HUVECs) but none investigating bioenergetics in PE while the second search retrieved studies exploring the technique in PE but none of the studies used HUVECs. Additional studies are required to investigate real-time mitochondrial bioenergetics in PE. Clearly, there is a need for more complete studies to examine the nuances of mitochondrial bioenergetics, focusing on the contributions of HUVECs in the context of PE.
Keywords: Bioenergetics; Metabolism; Oxidative stress; Preeclampsia